The coupling of the boundary solution procedures and the finite element methods applications in two-dimensional elastostatics - Adan, Edwin C. (1987)
This study is an attempt to show how the coupling of the boundary solution procedure and the finite element method can be used to solve two-dimensional elastostatic problems. The concepts of the finite element method and the boundary solution procedures are firstly presented. Next, the coupling of the procedures and the discretizaton of the boundary integral equations , which is the starting point in formulating a new boundary type element are then presented in detail. A suite of four computer programs are developed for this purpose. The results obtained using these programs attest to the capabilities of the coupling of the boundary solution procedure and finite element method.